2018
DOI: 10.1002/pc.25112
|View full text |Cite
|
Sign up to set email alerts
|

Thermal, Mechanical, and dielectric properties of Injection Molded Graphene Nanocomposites Based on ABS/PC and ABS/PP Blends

Abstract: In this research, graphene nanocomposites of poly(acrylonitrile‐butadiene‐styrene)/polycarbonate (ABS/PC) and ABS/polypropylene (ABS/PP) blends were prepared by melt blending and their thermal and mechanical properties were studied. The incorporation of graphene into ABS/PC and ABS/PP blends caused a significant decrease of their melt flow index values. Although graphene led to reduction of onset degradation temperature (Tonset) and maximum degradation rate temperature (Tpeak) of ABS/PC blends, and mainly of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…7 Yu et al 20 observed a synergistic effect of increasing the thermal conductivity of a PC/ABS commercial polymeric blend with the addition of 0.5 wt% GNP and some commercial additives (α-Al 2 O 3 and MgO particles). Triantou, Stathi & Tarantili 23 studied ABS/PC blend-based GNP nanocomposites with different blend ratios (70/30, 50/50, and 30/70), and verified that the GNP addition promoted different influence on the elastic modulus of the ABS/PC blend for different blend ratios. The same study also investigated the effect of ABS-g-MAH compatibilizer agent (10 wt%) on the ABS/PC blend, and found that the compatibilizer did not promote any positive effect on the ABS/PC compatibility at this content.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations
“…7 Yu et al 20 observed a synergistic effect of increasing the thermal conductivity of a PC/ABS commercial polymeric blend with the addition of 0.5 wt% GNP and some commercial additives (α-Al 2 O 3 and MgO particles). Triantou, Stathi & Tarantili 23 studied ABS/PC blend-based GNP nanocomposites with different blend ratios (70/30, 50/50, and 30/70), and verified that the GNP addition promoted different influence on the elastic modulus of the ABS/PC blend for different blend ratios. The same study also investigated the effect of ABS-g-MAH compatibilizer agent (10 wt%) on the ABS/PC blend, and found that the compatibilizer did not promote any positive effect on the ABS/PC compatibility at this content.…”
Section: Introductionmentioning
confidence: 88%
“…17 The addition of these nanofillers in the blends is made to improve the blend interfacial strength and to refine its morphology, producing high performance and multifunctional nanocomposites. 5,7,[18][19][20][21][22][23][24] Consequently, once PC/ABS blends are largely applied in automotive and electronic applications, 17,24 the use of carbon nanofillers as graphene nanoplates (GNP), 5,7,22,23 GO, 17 multi-walled carbon nanotubes (MWCNT), [18][19][20][21] and carbon black 24 have gained considerable attention of many researchers.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among carbon‐based nanomaterials, the remarkable properties of CNTs turned the attention of researchers for its diversified applications and proved to be exciting nanofiller for polymeric composites, energy‐storage devices, sensors, biomedical applications, and so forth. However, the commercial use CNTs in structural applications were limited due to their agglomeration tendency, high cost of production and some unresolved issues regarding the synthesis of high‐quality nanotubes …”
Section: Introductionmentioning
confidence: 99%